Characterization of Protein Radicals in Arabidopsis - Kumar, Aditya; Prasad, Ankush; Sedlářová, Michaela; Pospíšil, Pavel (Frontiers in Physiology, 2019)
Oxidative modification of proteins in photosystem II (PSII) exposed to high light has been studied for a few decades, but the characterization of protein radicals formed by protein oxidation is largely unknown. Protein oxidation is induced by the direct reaction of proteins with reactive oxygen species known to form highly reactive protein radicals comprising carbon-centred (alkyl) and oxygen-centred (peroxyl and alkoxyl) radicals. In this study, protein radicals were monitored in Arabidopsis exposed to high light by immuno-spin trapping technique based on the detection of 5,5-dimethyl-1-pyrroline N-oxide (DMPO) nitrone adducts using the anti-DMPO antibody. Protein radicals were imaged in Arabidopsis leaves and chloroplasts by confocal laser scanning microscopy using fluorescein conjugated with the anti-DMPO antibody. Characterization of protein radicals by standard blotting techniques using PSII protein specific antibodies shows that protein radicals are formed on D1, D2, CP43, CP47 and Lhcb3 proteins. Protein oxidation reflected by the appearance/disappearance of the protein bands reveals that formation of protein radicals was associated with protein fragmentation (cleavage of the D1 peptide bonds) and aggregation (cross-linking with another PSII subunits). Characterization of protein radical formation is important for better understating of the mechanism of oxidative modification of PSII proteins under high light.